Pakistan at 100 : From Poverty to Equity - Redaelli, Silvia (World Bank, Washington, DC, 2019)
This policy note was prepared in parallel to the report Pakistan at 100 – Shaping the Future. The report Pakistan at 100 discusses options to accelerate and sustain growth in Pakistan so that the country becomes an upper middle-income country when it turns 100 years old in 2047. This policy note discusses inequality of opportunities women face in Pakistan. Excluding women from the labor force means that a large share of Pakistan’s greatest asset, its population, is being wasted.